2016
DOI: 10.1038/ismej.2016.145
|View full text |Cite
|
Sign up to set email alerts
|

Use of plankton-derived vitamin B1 precursors, especially thiazole-related precursor, by key marine picoeukaryotic phytoplankton

Abstract: Several cosmopolitan marine picoeukaryotic phytoplankton are B1 auxotrophs requiring exogenous vitamin B1 or precursor to survive. From genomic evidence, representatives of picoeukaryotic phytoplankton (Ostreococcus and Micromonas spp.) were predicted to use known thiazole and pyrimidine B1 precursors to meet their B1 demands, however, recent culture-based experiments could not confirm this assumption. We hypothesized these phytoplankton strains could grow on precursors alone, but required a thiazole-related p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 42 publications
(55 reference statements)
7
73
0
Order By: Relevance
“…In another study, marine bacteria were shown to produce a thiazole precursor used by Ostreococcus species to synthesize thiamine. 36 These findings are analogous to our past findings in co-cultures of E. coli with A. protothecoides and indicate the widespread importance of cofactor symbiosis in promoting algae growth.…”
Section: Discussionsupporting
confidence: 78%
“…In another study, marine bacteria were shown to produce a thiazole precursor used by Ostreococcus species to synthesize thiamine. 36 These findings are analogous to our past findings in co-cultures of E. coli with A. protothecoides and indicate the widespread importance of cofactor symbiosis in promoting algae growth.…”
Section: Discussionsupporting
confidence: 78%
“…S7, Table S7). Our observations suggest that Euryarchaeota and Thaumarchaeota may be a source of vitamins B1 (thiamin), B2, B6, and B9 (folate) in the water column, analogous to observations on the provision of vitamins such as thiamin (B1) (Paerl et al 2017) and cobalamin (B12) (Bonnet et al 2010) by certain members of the community. This is further supported by the discovery of a complete cobalamin biosynthesis pathway in Thaumarchaeota (Doxey et al 2015).…”
Section: Archaeamentioning
confidence: 60%
“…In return, heterotrophic bacteria receive nutrients and can consume up to 82% of all algal-derived organic matter (Hornak et al, 2017). The release of vitamins and vitamin precursors by bacteria is one of the most common and well studied means mediating algaeÀbacteria interactions (Croft et al, 2005;Paerl et al, 2017). Vitamin transfer supports algal growth and can be considered as bacterial farming of algae as suppliers of organic resources.…”
Section: Cross-kingdom Exchange Of Resourcesmentioning
confidence: 99%